Effect of adolescent female fertility and healthcare spending on maternal and neonatal mortality in low resource setting of South Asia - Shongkour Roy; Tanjina Khatun (Health Economics Review, 2022)
Background: Maternal and neonatal mortality is high in South Asia. Recent studies have identifed factors such as adolescent female fertility, healthcare spending is reducing maternal and neonatal mortality. The objective of this study is to examine the efect of adolescent female fertility and healthcare spending on maternal and neonatal mortality in South Asian countries. Methods: A retrospective panel study design was used, a total of 8 South Asian countries (Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka) data from World development indicator 1990-2020 considered for analysis. Descriptive statistical method was used for summary. The efect of adolescent female fertility and healthcare spending on maternal and neonatal mortality were analysed using fxed and random efect regression with multiple imputation. Findings: Adolescent female fertility, maternal, and neonatal mortality is very high in the aforementioned countries, and considerably varies among countries. A signifcant relationship between the maternal mortality and healthcare spending, neonatal mortality and adolescent female fertility was observed. We found neonatal and maternal mortality are more likely to decrease depends on healthcare spending. Healthcare spending has a signifcantly negative efect on neonatal mortality (-0.182, 95% CI: [-0.295 to -.069]; P-value <0.01) and maternal mortality (-0.169, 95% CI: [-0.243 to -0.028]; P-value <0.05). A change in 1 % increases in healthcare spending should decrease by 0.182 neonatal mortality per 1000 live births and maternal mortality by 0.169 per 100,000 live births. Conclusions: In south Asian countries, increasing healthcare spending and decreasing adolescent female fertility may contribute to reduce maternal and neonatal mortality. In addition, number of service providers such as physicians supplied contributed to the decline of neonatal mortality. These fndings have important implications for future improvement of healthcare spending in maternal and neonatal health programs.
Keywords: 330; Neonatal mortality; Maternal mortality; Adolescent female fertility; Random efect model; Healthcarespending; Multiple imputation